Evaluation of the clinical effect of hyaluronic acid mouthwash on palatal secondary wound healing in diabetic rats - KURU, LEYLA; YILDIRIM, HATİCE SELİN (My University, 2023)
Objective: The objective of this study was to investigate clinical effect of topically administered hyaluronic acid (HA) mouthwash on healing of secondary palatal wound in diabetic (D) rats. Methods: 60 Wistar albino male rats were divided into D and non-diabetic (ND) groups. Diabetes was induced to 30 randomly selected rats by initially administering 110 mg/kg of nicotinamide intraperitoneally, followed by 15 min of intraperitoneal injection of 65 mg/kg of streptozotocin solution. 5 mm excisional wounds were made in the centre of the palate. After that, 6 animals from each group were sacrificed. Then, both groups were subdivided into two groups: 0.12% HA mouthwash and saline (S) (n=12 per group), depending on the agent to be administered to the wound area (WA). On days 7 and 14, six rats from each group were sacrificed, and the WAs were measured through photographic measurements utilizing Image J software. Results: The WA decreased with time in each group (p<0.05). A significant difference was detected in the intergroup comparison of the WA on days 7 and 14 (p<0.05). On days 7 and 14, the smallest WA was observed in the ND-HA group, while the largest was in the D-S group (p<0.05). On day 14, the WA of both HA groups was similar (p>0.05) and smaller than that of both S groups (p<0.05). Conclusion: Topical application of HA mouthwash effectively improved secondary wound healing and reduced WA in D and ND rats. Thus, topical application of HA can be used in diabetic palatal secondary wound healing.
Keywords: Wound healing; diabetes mellitus; hyaluronic acid; rat; palate